(untitled) (Journal Resuscitatio Balcanica, 2024)
The aim of this study is to analyze the basic epidemiological data related to OHCA and the impact of time intervals during the care of OHCA patients on their survival. Materials and Methods: Epidemiological data, data related to time intervals during the response and care process of OHCA patients, as well as outcome data for these patients, were analyzed in seven municipalities in Serbia. Data were collected as part of the EuReCa_Srbija program during the period from October 1, 2014, to December 31, 2021. Results: The overall annual incidence of recorded OHCA in the studied area was 137.43/100,000 inhabitants, while the annual incidence of initiating CPR measures was 50.16/100,000. In the group of patients with initiated CPR measures, a bystander initiated CPR in 16.98% of cases (annual incidence 8.52/100,000). Return of spontaneous circulation (ROSC) at the scene was recorded in 18.71% of cases with an annual incidence of 9.38/100,000, while in the same group, 15.49% of patients with ROSC were admitted to the hospital (annual incidence 7.77/100,000). The median response time of emergency medical services was 9.0 (IQR 5.0-17.0) minutes, the time from achieving ROSC to hospital arrival was 17.0 (IQR 12.0-27.0) minutes, and the time from departure from the cardiac arrest scene to hospital arrival was 9.5 (IQR 5.0-17.0) minutes. The cumulative proportion of ROSC was 50% after 5.6 kilometers traveled, or 5 minutes from the emergency call. ROSC at the scene was not recorded after 20 minutes from the emergency call, or after 11.2 kilometers traveled from the call reception to the scene. Conclusion: The incidence of OHCA in Serbia is comparable to that in other countries, with room for improvement in terms of greater layperson involvement in initiating CPR measures. The time intervals during the EMS response and care process for OHCA patients are longer compared to reports from other countries, indicating the need to modify factors that directly or indirectly affect these intervals.